Posture-reading by men’s football goalkeepers and other factors in saving penalty kicks - Sequeira,Manuel (2021)
ABSTRACT Penalty kicks are often decisive in football matches. Therefore, any technique that yields an advantage either in scoring or saving them is of great importance. Here we show the influence of a training programme for goalkeepers on the probability of defending penalties in men's football. Virtual training was used through an app that shows the shooter at the moment of setting the support foot on the ground and requiring the answer of which side (right or left) the ball will be directed at. Complemented with physical training, four sub 21 professional goalkeepers from Santarém, Brazil, developed the ability to correctly choose the side (left or right) at which the ball will be aimed. Sets of 800 penalties were kicked before (acting as control group) and after the training programme and it was found that, after training, the chances of saving penalty kicks or, at least, choosing the correct side, increase dramatically. It is concluded that the training programme improved the goalkeeper’s ability to choose the correct side. Other factors (laterality and height) were not found to be statistically significant.